FARMER PARTICIPATORY APPROACH FOR PREVENTION AND CONTROL OF LATE BLIGHT IN POTATO - Lal, Barsati; Prasad, B.; Sinha, T. K.; Singh, B. K; Pandey, N. K. (Potato Journal, 2013)
Late blight caused by Phytophthora infestans (Mont de Bary) is a serious disease of potato in Indo-gangetic alluvial plains of Bihar. Depending on severity, it can cause heavy yield losses ranging between 10 – 75%. Inprevious studies the disease was reported to be effectively controlled by the application of one spray of RidomilMZ(2.0 kg / ha) + one or two sprays of Mancozeb @ 2.0 kg/ha. In the present study this technique was refined using need based applications of fungicides. The study was conducted in 9 villages of Alampur-Gonpura panchayat of block Phulwarisharif in Patna district. In these villages, potato was observed to be an important crop covering a major area of land cultivated by the farmers. However, due to lack of proper knowledge and skill, farmers of these villages were found to use lower doses of fungicides resulting into ineffective disease control and reduction in potato yield. After identification of these problems, farmers’ participatory approach was applied and on-farm trials with early-maturing cultivar Kufri Ashoka were conducted under TAR / IVLP. These trials were conducted during 1999-2004 on 120 farmers-fields. Depending on occurrence of cool and humid weather, the first spray of Mancozeb @ 2.0 kg/ha was applied prophylactically in the 3rd or 4th week of December. Ridomil @ 2 kg/ha was applied in the 2nd spray after the disease appearance but not earlier than 10-11 days. The third and the last spray was applied 14-15 days later using Mancozeb @ 2.0 kg/ha. The results showed that the recommended doses and schedule of fungicidal sprays (T2) not only checked the late blight but also increased the yield over the plots treated with inadequate doses of fungicides by the farmerspractice (T1). The yield in scheduled fungicidal ranged between 215-260 q/ha as against 170-214 q/ha in plots treated as in farms practice. Thus, the improved practices of disease management could enable the farmers to get an additional yield of about 35-50 q/ha with extra return of Rs. 11,000/- to Rs. 19,000/- per ha. This refined spraying schedule has now been adopted by 80-90% of the farmers of surrounding villages also.